Avaliação do uso de linguagem documentária em catálogos coletivos de bibliotecas universitárias: um estudo sociocognitivo com protocolo verbal - Boccato, Vera Regina Casari [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The indexing language plays a fundamental role in the indexing and information retrieval. When the indexing language does not correspond to the necessities of representation of the contents of the documents, carried out by the indexers and the requests of bibliographical searches through the users’ subject, it affects the performance of those processes, compromising the accomplishment of searches and services. The proposal is to carry through an evaluation study of the alphabetic indexing language use of the online collective catalogs, with a main focus on the technologies of representation and information retrieval, in the perspective of the university libraries and in the socio-cognitive context of indexers and users. With the general objective of to contribute for the adequate use of the alphabetical indexing languages in the indexing and information retrieval processes of specialized scientific areas in collective catalogs of the university libraries and thus, to collaborate with the process of continuous changes in the librarians’ practice and, consequently, of its using community, the research had as specific objectives: arguing the role of the alphabetical indexing languages in the conception of the collective catalogs through the perspective of the online catalogs; presenting and arguing about the indexing languages evaluation studies through the quantitave, qualitative and qualitative-cognitive approaches as evaluation methods, which are supported by the theoretical and methodological fundamentals of the Organization and Knowledge Representation area, coping with the contemporary paradigms of the Information Science area ; and investigating the application of the socio-cognitive approach by Verbal Protocol for an evaluation study of the alphabetical indexing language use of the collective catalogs in specialized scientific areas in the perspective of the university libraries... (Complete abstract click electronic access below)

A linguagem documentária desempenha um papel fundamental na indexação e recuperação da informação. Quando a linguagem documentária não corresponde às necessidades de representação dos conteúdos dos documentos, realizada pelos bibliotecários indexadores e das solicitações de buscas bibliográficas por assunto dos usuários, afeta a atuação desses processos, comprometendo a realização de buscas e serviços. Realizou-se, como proposta, um estudo de avaliação do uso de linguagem documentária alfabética de catálogos coletivos online, com enfoque nas tecnologias de representação e recuperação da informação, na perspectiva das bibliotecas universitárias e no contexto sociocognitivo de bibliotecários indexadores e usuários. Com o objetivo geral de contribuir para o uso adequado de linguagens documentárias alfabéticas nos processos de indexação e recuperação da informação de áreas científicas especializadas em catálogos coletivos de bibliotecas universitárias e, deste modo, colaborar com o processo de mudanças contínuas nos fazeres bibliotecários e, consequentemente, nos de sua comunidade usuária, a pesquisa teve como objetivos específicos: discutir o papel das linguagens documentárias alfabéticas na concepção dos catálogos coletivos pela perspectiva dos catálogos online; apresentar e discutir os estudos de avaliação de linguagens documentárias pelas abordagens quantitativas, qualitativas e qualitativas-cognitivas como métodos de avaliação, subsidiados pelos fundamentos teóricos e metodológicos da área de Organização e Representação do Conhecimento, frente aos paradigmas contemporâneos da área de Ciência da Informação; e investigar a aplicação da metodologia qualitativa de abordagem sociocognitiva mediante Protocolo Verbal para estudo de avaliação do uso de linguagem documentária alfabética de catálogos coletivos...
Keywords: Linguagem documentária; Bibliotecas universitárias; Protocolo verbal; Organização e representação do conhecimento; Metodologia qualitativa sociocognitiva; Tecnologias de representação e recuperação da informação; Indexing Language; Evaluation; Qualitative-socio-cognitive methodology; Organization and Knowledge Representation; Public catalogs of online access; Representation and information retrieval technologies; University libraries; Verbal Protocol